Zawadzki i Kamsetzer – dowód przyjaźni i współpracy architektów. Rozważania o warszawskich pałacach Tyszkiewiczów i Raczyńskich - Mączyński, Ryszard (Sztuka i Kultura, 2021)
It is greatly inadequate in to-date research in Polish architecture of the Enlightenment period to almost completely lack reflection on the issue of the interrelation of its actual creators, especially those belonging to such an active artistic environment as Warsaw. The determinants shaping those ralations – like within every social-professional group – turn out to be diverse. It is not only the character-related issues of each of its members. It may be shaped by various communities: the national one and its derivative – linguistic, often also religious, attitudes resulting from a subjective sense of one’s own status or from holding a particular office, dependecies related to the previous cooperation, such as in the master-disciple or superior-subordinate relations. All those factors could be at work there, enhanced by the pressure of incessant competition within a profession, resulting from the necessity to provide oneself with an appropriate number of commissions. The previous lack of interest in delving into those relations on professional grounds is quite understood, as most often there are either no sources for it whatsoever, or they are fragmentary. The present article is an attempt to undertake such a consideration over the friendship and cooperation of two architects: a Pole – Stanisław Zawadzki (1743– 1806) and a Saxon – Johann Christian Kamsetzer (1753–1795). They both have their monographs, however, they are already quite dated, while containing a lot of gaps and superficial interpretations. The offices they respectively held, the architect of the crown troops and the National Education Commission for Zawadzki and king Stanisław August’s architect of court for Kamsetzer, did not twarth either of them in their realization of various works commissioned by private investors. However, the status of both architect-designers was different: Zawadzki was in charge of a building company and was an independent contractor, Kamsetzer on the other hand was dependent on Domenico Merlini, who held the most important office of the architect of His Majesty King and Poland, through which he had a decisive say in numerous issues. A ten-year age gap between Zawadzki and Kamsetzer mostly favoured their master-disciple relation, particularly because the former was notorious for being raised by St. Lucas Academy in Rome, while also being its di merito member as well as the winner of the Clementine Competition. There is no documentation preserved – relations, letters, notes – relating to the friendly bonds between Stanisław Zawadzki and Johann Christian Kamsetzer. There is, however, a piece of virtually undeniable evidence: in his artistic collection one of them had kept the sketchbooks of the other presented to him, filled with drawings made during the Italian trip of 1781. It seems that the cement of the friendship between Zawadzki and Kamsetzer was the sense of belonging to Mediterranean culture, a deep love for Italian art as well as their perceiving ancient culture as an embodiment of perfection. One could also risk a thesis that their mutual relations were strengthened by what was mastered by one of them and eluded the other. Zawadzki was a proficient illustrator, yet his disciplined line was the line of an architect, while Kamsetzer – which finds confirmation at least in his travel sketches – was a greatly talented illustrator and painter. A particular testimony to a fruitful cooperation of both architects can be found in two Warsaw residences: the palace of the Tyszkiewicz family in Krakowskie Przedmieście and the palace of the Raczyński family in Długa street. The Palace of the Tyszkiewicz family is a creation of the two architects. Stanisław Zawadzki made the initial version of its design most certainly as early as 1780, as in the very beginning of the following year a contract was signed between him and the commissioner Ludwik Tyszkiewicz, a Lithuanian field hetman. However, it was not until much later, in 1785, that the building works themselves actually began and proceded according to a somewhat modified project and revised agreement principles. In 1786, when the palace was already finished and in raw state, the supervision of the works was taken over – according to another contract signed with Tyszkiewicz – by Johann Christian Kamsetzer. His creative input was limited merely to designing a sumptuous moulding decorations of some of the interiors as well as designing the furniture or mirrors. There was no – unlike the researchers in the past suggested – change of designer who would modify the architectonic achievements of the predecessor. Kamsetzer merely decorated the building already erected by Zawadzki. It might be concluded that it was the very cooperation undertaken at the palace of the Tyszkiewicz family that initiated the future interaction of both architects and gave birth to their friendship. The palace of the Raczyński family was built in the years 1787–1789 for Kazimierz Raczyński, a crown marshall and the general of Greater Poland. Historians of the past had no doubts that it was the work of Kamsetzer, although there are too few solid source premises to confirm that thesis. However, while taking a closer and completely objective look (without being influenced by the attributions of old) at the composition of the front elevation, as well the plastic forms employed in its design, they will reveal great closeness to the ones used by Zawadzki, at least in the facade he had created a few years before to embellish the Piarist Palace of Collegium Nobilium. By contrast, they are completely unfamiliar to the rules followed by Kamsetzer. The former was dominated by austerity and monumentalism, the latter – finesse and ornateness. All the arguments of stylistic nature clearly point to the fact that the actual designer of the building was not Johann Christian Kamsetzer but Stanisław Zawadzki. Therefore, should the designer share of Kamsetzer be completely dismissed in the case of the capital city palace of the Raczyński family? It seems otherwise. There are his traits in the preserved decorations of the ball room as the rich mouldings reveal the artistic sense of Kamsetzer and his flair for the creation of this kind of decorations. Therefore, it seems that the palace of the Raczyński family can constitute, right after that of the Tyszkiewicz family, another example of both architects’ cooperation on a single work. A cooperation proceding deftly and smootly as it resulted from their natural conditioning and talents. The work of the architect was later completed by the interior designer. It should be underlined that it was a frequent practice in Stanislavian times, and its idea was contained in the very contract, which pointed out that the ornaments (mouldings, frescoes) in the erected building would belong to a separate team of artists specializing it this particular area. The interior design was still in the hands of the investor and, as an especially important domaine, it was not infrequently treated as a distinct and independent stage of building works. Therefore, the realization of the capital city palace of the Tyszkiewicz family must bear testimony to the cooperation of both architects, Zawadzki and Kamsetzer, and not an argument for the competition between them as it has so far been wrongly interpreted. Their role in the erection of the Warsaw residence of the Raczyński family should be regarded likewise.